2021
DOI: 10.5811/westjem.2021.3.50932
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Mechanical Chest Compression Devices over Manual Cardiopulmonary Resuscitation: A Systematic Review with Meta-analysis and Trial Sequential Analysis

Abstract: Introduction: Our goal was to systematically review contemporary literature comparing the relative effectiveness of two mechanical compression devices (LUCAS and AutoPulse) to manual compression for achieving return of spontaneous circulation (ROSC) in patients undergoing cardiopulmonary resuscitation (CPR) after an out-of-hospital cardiac arrest (OHCA). Methods: We searched medical databases systematically for randomized controlled trials (RCT) and observational studies published between January 1, 2000–Oct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 43 publications
2
20
0
Order By: Relevance
“…In our TSA ( Figure 2 B and Figure 3 B), after accumulating recent cohort studies, we found that the cumulative Z-curve finally crossed into the O’Brien-Fleming boundaries and showed the true-positive effects of mechanical CPR. This overturns the conclusion of no benefit for short-term survival outcomes in the use of mechanical CPR in the recent SRMA [ 8 , 45 ]. For the outcomes of ROSC and survival to hospital admission, the requirement of adequate sample size for statistical power was not met.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…In our TSA ( Figure 2 B and Figure 3 B), after accumulating recent cohort studies, we found that the cumulative Z-curve finally crossed into the O’Brien-Fleming boundaries and showed the true-positive effects of mechanical CPR. This overturns the conclusion of no benefit for short-term survival outcomes in the use of mechanical CPR in the recent SRMA [ 8 , 45 ]. For the outcomes of ROSC and survival to hospital admission, the requirement of adequate sample size for statistical power was not met.…”
Section: Discussionsupporting
confidence: 59%
“…To date, 10 systematic reviews have been published to compare the effects of manual CPR and mechanical CPR on cardiac arrest [ 8 , 9 , 10 , 11 , 12 , 45 , 46 , 47 , 48 , 49 ]. Among them, five systematic reviews focused on OHCA [ 8 , 10 , 11 , 45 , 48 ], four systematic reviews, including one Cochrane review, enrolled both OHCA and IHCA [ 9 , 12 , 46 , 49 ], and one review involved in IHCA [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a 2021 meta-analysis examining the effectiveness of mechanical chest compression devices, 20 15 studies (n=18,474) were analyzed: 6 randomized controlled trials, 2 cluster randomized controlled trials, 5 retrospective case-control studies, and 2 phased prospective cohort studies. The pooled estimate summary effect did not indicate a significant difference in achieving ROSC between mechanical and manual compression (Mantel-Haenszel OR 1.16, 95% CI 0.97–1.39; p=0.11, I2=0.83).…”
Section: Discussionmentioning
confidence: 99%